Comparison of the Sensitivity of Arabidopsis SOS Pathway Mutants under Salt Stress - Abudureyimu, Buasimuhan; Aksoy, Emre (Turkish Journal of Agriculture - Food Science and Technology, 2019)
Salinity stress is one of the most important and common abiotic stress factors that cause significant physiological and metabolic changes in plants, negatively affecting plant growth and development, and causing decrease in product quality and quantity. The elucidation of the molecular control mechanisms associated with salt stress tolerance is based on the activation and /or inactivation of various stress-related genes. Salt Overly Sensitive (SOS) tolerance mechanism under salt stress is of great importance in terms of salt tolerance of the plants. Although this mechanism has been studied for many years, the physiological changes that the plants give as a result of mutation of the genes in the pathway under different levels of sodium chloride (NaCl) during development have not been examined comparatively. In this study, we found that the Arabidopsis thaliana sos1-1 mutant plant showed sensitivity to 10 mM NaCl while the sos3-1 and hkt1-1 mutants showed tolerance. The sos1-1, sos3-1 and hkt1-1 mutants showed increasing sensitivity when NaCl was applied beyon 50 mM of concentration. In addition, plants did not show significant sensitivity for 1 day of stress application, while significant effects were observed in plant root length when exposed to salinity for 3 to 4 days. Col-0, hkt1-1 and sos3-1 roots treated with low levels of NaCl for a short term were positively affected in length. In the light of these results, the amount and duration of salt stress is very critical in Arabidopsis thaliana’s responses to the stress and determination of molecular tolerance pathways.